KESIAPAN SARANA DAN PRASARANA PENDIDIKAN PADA SEKOLAH MENENGAH ATAS DI ERA NEW NORMAL - Fitriani Fitriani (Didaktika : Jurnal Kependidikan, 2022)
This study aims to describe the readiness of educational facilities and infrastructure in the New Normal Era at UPT SMAN 9 Bone and MAN 1 Bone to describe the learning process in the New Normal Era at UPT SMAN 9 Bone and MAN 1 Bone. This research uses a qualitative approach with the type of multi-case study research. Data collection techniques are the method of observation, interviews and documentation. The data that has been collected is then analyzed through the stages of data reduction, data display and drawing conclusions. The results of the research are 1) The readiness of educational facilities and infrastructure in welcoming learning in the new normal era at UPT SMAN 9 Bone and MAN 1 Bone can be said to be available even though not all facilities can be categorized as adequate, 2) Learning in the new normal era at UPT SMAN 9 Bone and MAN 1 Bone uses a blended learning method by combining face-to-face learning and online learning simultaneously.Keywords: 3-5 keywords from article, separated by semicolon